2020
DOI: 10.1177/1747493020937192
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke shoulder pain in subacute patients and its correlation with upper limb recovery after robotic or conventional treatment: A secondary analysis of a multicenter randomized controlled trial

Abstract: Background and aims Poststroke shoulder pain is a common complication. We aimed to investigate the prevalence of poststroke shoulder pain, with attention to the neuropathic component, and the relationship between poststroke shoulder pain and upper limb improvement in motor function, strength, disability, and quality of life after upper limb rehabilitation. Methods This is a secondary analysis of a multicen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…A full report of the data extracted from the included studies is presented in a structured synoptic table (Additional file 1 : Append ix 1) [ 13 , 25 – 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…A full report of the data extracted from the included studies is presented in a structured synoptic table (Additional file 1 : Append ix 1) [ 13 , 25 – 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in our sample, pain showed a moderate but non-significant correlation with upper limb activity performance. Previous studies reported that the baseline intensity of pain in the paretic shoulder is related to motor performance, quality of life, and motor functions, and negatively impacts the recovery of upper limb function [ 39 ]. It is possible that the absence of a significant correlation in our work is partly explained by a lack of statistical power as a result of the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the wide multicenter trial for the evaluation of robot-assisted training for the upper limb after stroke (RATULS) has demonstrated that robotic neurorehabilitation does not significantly improve the upper limb function (62). Pain intensity has been positively correlated with time since stroke and negatively with motor function (44), supporting the need to examine the role of robot-assisted rehabilitation in pain processing and to clear the mechanisms necessary for effective functional gain. The latter is a top ten priority for stroke survivors (63).…”
Section: Discussionmentioning
confidence: 99%
“…Different researchers/operators will independently recruit patients, generate the allocation sequence, and assign participants to interventions and no member of the trial will have access to the codes up to the end. Both males and females will be enrolled due to differences in baseline pain perception (44) and to sex-treatment interactions (45). Therefore, no blocking will occur but minimization will be performed for sex-difference in pain perception, handled to ensure that any individual who might introduce bias is not involved (46).…”
Section: Recruitment Allocation Concealment and Blindingmentioning
confidence: 99%